Creating Colonial Williamsburg : The Restoration of Virginia's Eighteenth-Century Capital - Greenspan, Anders (Book collections on Project MUSE., 2009)
In Creating Colonial Williamsburg, Anders Greenspan examines the restoration and re-creation of the structures and gardens of Virginia's colonial capital beginning in 1926. The restoration was undertaken by the Rockefeller family, whose aim was to promote a twentieth-century appreciation for eighteenth-century ideals. Ironically, those ideals, including democracy, individualism, and representative government, were often promoted at the expense of a more complete understanding of the town's true history. The meaning and purpose of Colonial Williamsburg has changed over time, along with America'